A rare presentation of massive subamniotic hemorrhage in a pregnant woman with severe malaria: A case report - Mesfin Ayalew Tsegaye, MD; Abel Benti Abchale, MD; Matyas Wondwossen Elssa, MD; Kefelegn Negalign Mekuria, MD; Negusu Kassa Biza, MD; Fitsum Assefa Gemechu, MD; Rebecca Haile Tesfay, MD (Radiology Case Reports, 2025)
Malaria during pregnancy poses significant health risks, leading to severe complications such as anemia, thrombocytopenia, and placental bleeding. Severe Plasmodium falciparum infection can result in placental hematomas, which may be classified as retroplacental, subchorionic, or subamniotic. Subamniotic hemorrhages, although rare may contribute to adverse outcomes such as preterm delivery and fetal growth restriction. This case report details a 28-year-old mother who experienced massive subamniotic bleeding due to severe malaria, ultimately leading to preterm delivery. The mother recovered after having minimal bleeding after the delivery, while the neonate died at the neonatal ICU due to complications of prematurity. The placenta was found to contain approximately 800 mL of lysed blood, highlighting the serious implications of malaria on pregnancy outcomes. This report emphasizes the importance of early detection and management of placental hematomas in pregnant women with malaria to mitigate risks for both the mother and fetus. Enhanced awareness among healthcare providers is crucial for improving maternal and neonatal health in malaria-endemic regions.